Paroxysmal nocturnal hemoglobinuria: a case report in a pandemic environment - Peixoto, Vanda (2023)
Paroxysmal nocturnal hemoglobinuria (PNH) is a clonal, rare, complement-mediated hemolytic anemia. PNH can be associated with marrow failure and thrombophilia. We present a clinical report of splenic vein thrombosis in a patient with classic PNH. A 41-year-old male with classic PNH, naïve to complement inhibitor therapy, developed splenic vein thrombosis as a major adverse effect after vaccination protocol to prevent meningococcal disease. We also report anticoagulant and eculizumab treatment outcomes. In PNH patients, vaccination should be monitored to prevent major outcome events, like vaccine-induced thrombosis. Eculizumab proves effective for treating intravascular hemolysis and preventing more thrombotic events. The potential protective role of eculizumab on controlling complement activity and consequent inflammation may help the patient to not experience breakthrough hemolysis when infected with SARS-CoV-2. Extravascular hemolysis remains present, but new molecules are being studied to inhibit proximal complement and there is a good health prospective for PNH patients.